Filipino Americans - Yoder, Carolyn P. 1953- (Chicago Heinemann Library, 2003)
An overview of the history and daily lives of people from the Philippines who immigrated to the United States.
Keywords: Filipino Americans -- History -- Juvenile literature; Filipino Americans -- Social life and customs -- Juvenile literature; Filipino Americans